(3CHMGK aj GdGadGSs - (3SejQ aQfGf(B, (3HGdjs; (3aQfGf HGdj(B, s ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3WHjYI GdOjhf GdeHQQI dTgQ GdGadGS h UaGJgG , GdGJaGbjI GdbVGFjI GdShQjI GddHfGfjI , VO ef jLH Ydi GdeadS Cf jhLg GSJFfGag ddMce GdPj bVi HTgQ EadGSg , VO hcjd dJadjSg, Ce VO GdOGFf WGdH TgQ GdGadGS , Ce VOgeG eYG , eJi JHOC GdehGYjO GdbGfhfjI dWQb GdWYf VO GdMce GdUGOQ HQO OYhi GdGadGS , gd jLhR GdedGMbI GdLRGFjI HLQGFe GdGadGS bHd UOhQ Mce HTgQ GdGadGS Yf GdeMceI GdHOGFjI GdeOfjI GdeNJUI , GdNGVYhf dfXGe GdGadGS , bVGjG EadGSjI (B.s
Keywords: (3GdEadGSs; (3GdOjhfs; (3LQGFe GdCehGds